Modifying the surface wetting behavior of soda-lime silicate glass substrates through thermal poling - Lind, F.; Palles, Dimitrios; Moencke, D.; Kamitsos, E. I.; Wondraczek, Lothar (Journal of Non-Crystalline Solids, 2017)
Thermal poling, i.e., exposure of a glass to a DC electrical field at moderate temperature, enables the generation of an anisotropic surface layer. Cation motion on the anode side results in the formation of an internal gradient in the electrical potential which can be frozen-in upon cooling. This is accompanied with a change in the polarity of the anode surface and, hence, a change in surface wettability. In this article, we study the effect of thermal poling on the wettability of soda-lime silicate glasses. We confirm a poling-induced increase in surface hydrophobicity on the air-side of commercial float glass, with a water wetting angle increase of around 20° for poling at 210 °C and 1.5 kV. The effect is persistent after storage for three months under ambient conditions. Significant variation between air and tin-side of the float glass indicates strong compositional dependence and offers a route for tailoring the surface chemical properties of functional glass substrates.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Glass surface; Soda lime silicate; Thermal poling; Wetting angle